2021
DOI: 10.3390/antiox10091439
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress and Oxidative Stress as Common Factors of the Pathogenesis of Depression and Alzheimer’s Disease: The Role of Antioxidants in Prevention and Treatment

Abstract: There is a growing body of scientific research showing the link between depression and dementia in Alzheimer’s disease (AD). The chronic stress contributes to the formation of oxidative stress in the parts of the brain involved in the development of depression and AD. The scientific literature reports the significant role of antioxidants, which are highly effective in treating these diseases. In this review, we have summarized the relationship between chronic stress, oxidative stress, and the changes in the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 257 publications
(366 reference statements)
0
42
0
Order By: Relevance
“…Therefore, much work has gone into developing antioxidant treatments as neuroprotective drugs for AD [ 132 ]. Published work showed that OS plays a vital role in advancing AD, and antioxidants act against OS damaging effects [ 133 ].…”
Section: Neuroprotective Mechanisms Of Natural Products For Admentioning
confidence: 99%
“…Therefore, much work has gone into developing antioxidant treatments as neuroprotective drugs for AD [ 132 ]. Published work showed that OS plays a vital role in advancing AD, and antioxidants act against OS damaging effects [ 133 ].…”
Section: Neuroprotective Mechanisms Of Natural Products For Admentioning
confidence: 99%
“…The major physiological effects of curcumin are anti-inflammatory and antioxidant effects [ 9 ], and responses occur through a decrease in the expression of pro-inflammatory genes. Therefore, curcumin has been shown to cure various diseases, including cancer, heart failure, and Alzheimer’s dementia [ 21 , 22 , 23 ]. In addition, curcumin exerts analgesic effects on acute and chronic pain by de-sensitizing the transient receptor potential vanilloid 1, an ion channel responsible for pain sensation, thereby reducing pain sensitivity [ 24 , 25 ].…”
Section: Curcuminmentioning
confidence: 99%
“…Under normal settings, the dynamic balance between ROS and antioxidants is maintained; nevertheless, when the body is stressed, hyperactivation of active oxygen free radicals occurs, resulting in an imbalance of an organism's oxidation system. These effects cause mitochondrial damage, elevated levels of NO, MDA, and cytokine, a decrease in antioxidant activity (such as SOD, CAT, and GSH), hippocampus neuronal damage, apoptotic process, and depression, or worsening of the depression course ( 49 , 50 ). Herein, MDA levels in the hippocampus of CSDS mice were found considerably higher, while CAT, SOD, and GSH levels were affectedly lowered.…”
Section: Discussionmentioning
confidence: 99%